2019
DOI: 10.21577/0103-5053.20190078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fatty Acid Methyl Ester Composition, Acid Value, and Water Content on Metallic Copper Corrosion Caused by Biodiesel

Abstract: Oxidative stability parameters (OSP), acid value (AV), water content (W), and the metallic copper corrosion rate in biodiesels obtained from eight different vegetable oils were determined. Simple and multiple linear regression models were constructed to explain the influence of the OSP, AV and W variables on the corrosion rate. The corrosion rate was lower in biodiesel with less oxidative stability because, instead of reacting with copper, O 2 reacted preferentially with the unsaturated fatty acid methyl ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…No comparative values for these corrosion rates from pure MS, MO, or ML are available, but the effect of the unsaturation C=C on the corrosion rate in the mixtures is evident. Mass loss tests of biodiesel synthesized from several oils in the presence of oxygen have reported a similar tendency in corrosion rates [7,40,41]. Easily oxidizable biodiesel has many unsaturated molecules and is less corrosive.…”
Section: Mass Loss Measurementsmentioning
confidence: 84%
See 1 more Smart Citation
“…No comparative values for these corrosion rates from pure MS, MO, or ML are available, but the effect of the unsaturation C=C on the corrosion rate in the mixtures is evident. Mass loss tests of biodiesel synthesized from several oils in the presence of oxygen have reported a similar tendency in corrosion rates [7,40,41]. Easily oxidizable biodiesel has many unsaturated molecules and is less corrosive.…”
Section: Mass Loss Measurementsmentioning
confidence: 84%
“…mixtures is evident. Mass loss tests of biodiesel synthesized from several oils in the presence of oxygen have reported a similar tendency in corrosion rates [7,40,41]. Easily oxidizable biodiesel has many unsaturated molecules and is less corrosive.…”
Section: Mass Loss Measurementsmentioning
confidence: 84%
“…For example, high SFA content and a lack of PUFAs (i.e., a lower degree of unsaturation comparative to other strains) resulted in lower IV values. These properties generally indicate superior oxidative stability (Rocha Jr et al, 2019). However, allylic position equivalents (APE) and bis‐allylic position equivalents (BAPE) are better indicators of oxidative stability than IV (Knothe, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Allylic sites are where a methylene (CH 2 ) group is located adjacent to one double bond. They are highly susceptible to oxidation, but bis‐allylic sites are even more susceptible due to the location of the methylene group between two double bonds (Rocha Jr et al, 2019). Given the lack of PUFAs in the Synechococcus strains, predicted OS values of zero (Table 3) are surprising.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlighted that the choice of emulsifiers, fuel-water ratio, and other factors were crucial for ensuring the long-term sustainability and performance of equipment that came in contact with diesel emulsion fuels. Rocha et al (2019) investigated the impact of biodiesel properties on the corrosion of metallic copper. The study found that the composition of FAME in biodiesel, as well as the acid value and water content, could significantly influence the corrosion of copper.…”
Section: Copper and Its Alloymentioning
confidence: 99%